Subject Phenomenon in German - Edy Hidayat (Nusantara Science and Technology Proceedings)
Sentences are not only analyzed syntactically but also semantically. One then no longer speaks about syntactic aspects of the subjects, objects or predicates. A classification of the subjects from a semantic point of view mostly occurs according to the meaning structure of the verbs. Subjects therefore not only play the role as agents but also as Ursache, Zustandsträger, and even as patients. It is often understood that the subject does something in a sentence, i.e. as the perpetrator. The Data are described qualitatively based on the semantic functions of each subject. The subjects in the sentences Peter hat Fieber and Die Mutter wäscht die Hemden have different semantic functions. Besides verbs, there are other factors that determine the role of the subjects. The various semantic functions of the subjects in German sentences are discussed in this paper.